Effect of continuously flowing liquid Li limiter on particle and heat fluxes during H-mode discharges in EAST. (October 2022) - Zuo, G.Z.; Li, C.L.; Maingi, R.; Meng, X.C.; Andruczyk, D.; Sun, P.J.; Sun, Z.; Xu, W.; Huang, M.; Tang, Z.L.; Zhang, D.H.; Chen, Y.J.; et al.
Highlights: Particle and heat fluxes were successfully controlled by using continuously flowing liquid Li (FLiLi) limiter in the H mode discharges with high plasma heating power in EAST. By using flowing liquid Li limiter, the fuel recycling could effectively reduce by ∼ 50% and Zeff could decrease from 2.3 to 1.6. The decreased recycling and impurity radiation led to the achievement of high energy confinement plasma with the average stored energy increased up to ∼ 290 kJ. Due to Li vapor shielding effect, ∼40% plasma heat flux was dissipated before arrived at the Li limiter. Abstract: Particle and heat fluxes were successfully controlled by using a continuously flowing liquid Li (FLiLi) limiter in the H-mode discharges with high plasma heating power in the Experimental Advanced Superconducting Tokamak device. There were strong interactions between the FLiLi limiter and high-power plasma with a ∼ 8.3 MW source heating power, and successively, a bright Li radiation ring was produced, which effectively decreased fuel particle recycling by approximately 50%. Due to Li efflux from FLiLi during a series of high-power discharges, an obvious real-time wall conditioning effect was produced, and fuel particle recycling further decreased. Moreover, the value of Zeff decreased from 2.3 to 1.6 due to a decrease in impurity sources; this was attributed to the accumulation of Li deposited on the first wall, which effectively protected the wall materials. The decreased recycling and impurity radiation achieved high-energy confinement plasma, and the average stored energy increased up to ∼ 290 kJ. Moreover, due to the effect of Li vapor shielding, nearly 30% plasma heat flux was dissipated before it arrived at the Li limiter. These results promote further exploration of liquid Li solutions for the critical challenge of heat flux handling and particle control in fusion power plants.